2018
DOI: 10.1002/hep.30097
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl‐CoA Carboxylase Inhibition Reverses NAFLD and Hepatic Insulin Resistance but Promotes Hypertriglyceridemia in Rodents

Abstract: Pharmacologic inhibition of acetyl-CoA carboxylase (ACC) enzymes, ACC1 and ACC2, offers an attractive therapeutic strategy for nonalcoholic fatty liver disease (NAFLD) through simultaneous inhibition of fatty acid synthesis and stimulation of fatty acid oxidation. However, the effects of ACC inhibition on hepatic mitochondrial oxidation, anaplerosis, and ketogenesis in vivo are unknown. Here, we evaluated the effect of a liver-directed allosteric inhibitor of ACC1 and ACC2 (Compound 1) on these parameters, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
178
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(189 citation statements)
references
References 44 publications
9
178
1
1
Order By: Relevance
“…), and pharmacological inhibition of ACC can decrease hepatic DNL and hepatic steatosis (Goedeke et al . ). This is, however, at the expense of hypertriglyceridaemia (Goedeke et al .…”
Section: Hepatic Lipid and Carbohydrate Handling Hepatic De Novo Lipmentioning
confidence: 97%
See 1 more Smart Citation
“…), and pharmacological inhibition of ACC can decrease hepatic DNL and hepatic steatosis (Goedeke et al . ). This is, however, at the expense of hypertriglyceridaemia (Goedeke et al .…”
Section: Hepatic Lipid and Carbohydrate Handling Hepatic De Novo Lipmentioning
confidence: 97%
“…This is, however, at the expense of hypertriglyceridaemia (Goedeke et al . ). In human‐derived HEPG2 cells, addition of fructose to glucose does not further upregulate ACC expression (Hirahatake et al .…”
Section: Hepatic Lipid and Carbohydrate Handling Hepatic De Novo Lipmentioning
confidence: 97%
“…These findings have now been validated in a phase II trial of a liver-targeted, allosteric inhibitor of ACC1 and ACC2, which demonstrated reduced hepatic steatosis and improved markers of fibrosis. (5) Hypertriglyceridemia, an unanticipated response to long-term ACC inhibition, has been observed in both rodents (4,6) and humans. (5,6) Goedeke et al (4) as well as Kim et al (6) have now shed light on this phenomenon as a previously unappreciated mechanistic point of control in triglyceride metabolism.…”
Section: See Article On Page 2197mentioning
confidence: 99%
“…Liver-directed inhibition of ACC1 and ACC2 reduces de novo lipogenesis and increases fatty acid β-oxidation. (4,6) Despite reductions in triglycerides content in the liver and improvements in insulin sensitivity, liver-directed inhibition of ACC1 and ACC2 leads to a decrease in polyunsaturated fatty acids and an increase in SREBP1c, GPAT1 expression and VLDL secretion, eventually leading to hypertriglyceridemia. Fibrate drugs decrease plasma triglycerides by enhancing fatty acid oxidation in the liver and by promoting lipoprotein lipase-mediated triglyceride clearance from the plasma.…”
Section: See Article On Page 2197mentioning
confidence: 99%
See 1 more Smart Citation